PEMANFAATAN GOOGLE SITES SEBAGAI MEDIA PEMBELAJARAN MATEMATIKA INTERAKTIF: SYSTEMATIC LITERATURE REVIEW - Nursaidah, Nursaidah; Nandang Mustafa, Ade (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the utilization of Google Sites as an interactive mathematics learning medium through a Systematic Literature Review (SLR) approach. Unlike previous studies that examined web-based learning media in general, this study specifically maps the use of Google Sites in the context of mathematics learning, encompassing research trends, development models, integration of learning approaches, and its effectiveness across various educational levels. The SLR method was applied using the PICOC framework, with article selection following the PRISMA protocol through Google Scholar and Scopus databases, covering publications from 2021 to 2026. A total of 31 articles were selected after going through identification, screening, and inclusion stages managed using the Covidence application. The results indicate a significant upward trend, with R&D methods dominating (39%) and the majority of studies conducted at the Junior High School level. Google Sites development was widely integrated with Problem Based Learning, Flipped Classroom Discovery Learning, and ethnomathematics approaches using the ADDIE and 4D models. Google Sites proved effective in improving students' learning outcomes, motivation, and interest in mathematics across various educational levels, with validity and practicality ratings consistently in the valid to very valid category. This study recommends that mathematics teachers integrate Google Sites with active learning models to optimize student learning outcomes.